Zeta and Related Functions - 26.3 Lattice Paths: Binomial Coefficients
DLMF | Formula | Constraints | Maple | Mathematica | Symbolic Maple |
Symbolic Mathematica |
Numeric Maple |
Numeric Mathematica |
---|---|---|---|---|---|---|---|---|
26.3.E1 | \binom{m}{n} = \binom{m}{m-n} |
binomial(m,n) = binomial(m,m - n)
|
Binomial[m,n] == Binomial[m,m - n]
|
Failure | Successful | Successful [Tested: 6] | Successful [Tested: 6] | |
26.3.E1 | \binom{m}{m-n} = \frac{m!}{(m-n)!\,n!} |
binomial(m,m - n) = (factorial(m))/(factorial(m - n)*factorial(n))
|
Binomial[m,m - n] == Divide[(m)!,(m - n)!*(n)!]
|
Successful | Successful | Skip - symbolical successful subtest | Successful [Tested: 6] | |
26.3.E2 | \binom{m}{n} = 0 |
binomial(m,n) = 0
|
Binomial[m,n] == 0
|
Failure | Failure | Successful [Tested: 3] | Successful [Tested: 3] | |
26.3.E3 | \sum_{n=0}^{m}\binom{m}{n}x^{n} = (1+x)^{m} |
|
sum(binomial(m,n)*(x)^(n), n = 0..m) = (1 + x)^(m)
|
Sum[Binomial[m,n]*(x)^(n), {n, 0, m}, GenerateConditions->None] == (1 + x)^(m)
|
Successful | Successful | - | Successful [Tested: 0] |
26.3.E4 | \sum_{m=0}^{\infty}\binom{m+n}{m}x^{m} = \frac{1}{(1-x)^{n+1}} |
sum(binomial(m + n,m)*(x)^(m), m = 0..infinity) = (1)/((1 - x)^(n + 1))
|
Sum[Binomial[m + n,m]*(x)^(m), {m, 0, Infinity}, GenerateConditions->None] == Divide[1,(1 - x)^(n + 1)]
|
Successful | Successful | - | Successful [Tested: 3] | |
26.3.E5 | \binom{m}{n} = \binom{m-1}{n}+\binom{m-1}{n-1} |
binomial(m,n) = binomial(m - 1,n)+binomial(m - 1,n - 1)
|
Binomial[m,n] == Binomial[m - 1,n]+Binomial[m - 1,n - 1]
|
Successful | Successful | - | Successful [Tested: 6] | |
26.3.E6 | \binom{m}{n} = \frac{m}{n}\binom{m-1}{n-1} |
binomial(m,n) = (m)/(n)*binomial(m - 1,n - 1)
|
Binomial[m,n] == Divide[m,n]*Binomial[m - 1,n - 1]
|
Successful | Successful | - | Successful [Tested: 6] | |
26.3.E6 | \frac{m}{n}\binom{m-1}{n-1} = \frac{m-n+1}{n}\binom{m}{n-1} |
(m)/(n)*binomial(m - 1,n - 1) = (m - n + 1)/(n)*binomial(m,n - 1)
|
Divide[m,n]*Binomial[m - 1,n - 1] == Divide[m - n + 1,n]*Binomial[m,n - 1]
|
Successful | Successful | - | Successful [Tested: 6] | |
26.3.E7 | \binom{m+1}{n+1} = \sum_{k=n}^{m}\binom{k}{n} |
binomial(m + 1,n + 1) = sum(binomial(k,n), k = n..m)
|
Binomial[m + 1,n + 1] == Sum[Binomial[k,n], {k, n, m}, GenerateConditions->None]
|
Successful | Successful | - | Successful [Tested: 6] | |
26.3.E8 | \binom{m}{n} = \sum_{k=0}^{n}\binom{m-n-1+k}{k} |
binomial(m,n) = sum(binomial(m - n - 1 + k,k), k = 0..n)
|
Binomial[m,n] == Sum[Binomial[m - n - 1 + k,k], {k, 0, n}, GenerateConditions->None]
|
Successful | Successful | - | Failed [3 / 6]
Result: Indeterminate
Test Values: {Rule[m, 1], Rule[n, 1]}
Result: Indeterminate
Test Values: {Rule[m, 2], Rule[n, 2]}
... skip entries to safe data | |
26.3.E9 | \binom{n}{0} = \binom{n}{n} |
|
binomial(n,0) = binomial(n,n)
|
Binomial[n,0] == Binomial[n,n]
|
Successful | Successful | - | Successful [Tested: 3] |
26.3.E9 | \binom{n}{n} = 1 |
|
binomial(n,n) = 1
|
Binomial[n,n] == 1
|
Successful | Successful | - | Successful [Tested: 3] |
26.3.E10 | \binom{m}{n} = \sum_{k=0}^{n}(-1)^{n-k}\binom{m+1}{k} |
binomial(m,n) = sum((- 1)^(n - k)*binomial(m + 1,k), k = 0..n)
|
Binomial[m,n] == Sum[(- 1)^(n - k)*Binomial[m + 1,k], {k, 0, n}, GenerateConditions->None]
|
Successful | Failure | - | Successful [Tested: 6] |